Re-theorizing literacy practices complex social and cultural contexts - Bloome, David; Castanheira, Maria Lucia; Leung, Constant 1950-; Rowsell, Jennifer 1969- (Routledge, 2019)
"Moving beyond the current theories on literacy practices, this edited collection sheds new light on the complexities inherent to the social, cultural, and ideological contexts in which literacy practices are realized. Building on Brian V. Street's scholarship, contributors discuss literacy as innately social and ideological, and examine how the theorizing of literacy practices has evolved in recognition of the diverse contexts in which written language is used. Breaking new intellectual and theoretical ground, this book brings together leading literacy scholars to re-examine how educational and sociocultural contexts frame and define literacy events and practices. Drawing from the richness of Brian V. Street's work, this volume offers insights into fractures, tensions, and developments in literacy for scholars, students, and researchers"--